THE EFFECT OF INNOPROVET PROBIOTICS ON RABBIT MEAT QUALITY AND VETERINARY SANITARY ASSESSMENT - Ibragimov F. M.; Ibragimov F. B. (Web of Journals Publishing, 2024)
This article publishes the results of the assessment of meat obtained from rabbits from a veterinary Sanitary Unit, the composition of which is carried out when rabbits being raised for meat are given the probiotic “Innoprovet”.
Keywords: Slaughter output, slaughter weight, tissue, pepton, occiproline, tryptophan, cell, live weight, carnivory index, probiotic, innoprovet.